PORTRAIT OF COUNSELORS' SELF-EFFICACY IN THE IMPLEMENTATION OF INDIVIDUAL COUNSELING SERVICES IN SCHOOLS - Elia Firda Mufidah; Husni Abdillah; Ana Himatul Habibah (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to describe the self-efficacy of counselors in the implementation of individual counseling services in schools, as well as identify factors that affect the success and failure in counseling practice. The self-efficacy of counselors is an important aspect that determines the quality of intervention and success in helping students overcome their problems. This study uses a descriptive qualitative approach with data collection techniques through open questionnaires and narrative analysis of the experiences of secondary school counselors. The results showed that the self-efficacy of counselors was closely correlated with the mastery of basic counseling skills, such as building empathic relationships, using appropriate techniques, and the ability to read students' psychological dynamics. The success of individual counseling is characterized by positive changes in student behavior, increased self-confidence, and intrapersonal and interpersonal conflict resolution. Meanwhile, the failure of counseling services is largely caused by low self-efficacy, lack of environmental support, inappropriate approaches, and difficulties in establishing therapeutic relationships. This study recommends the need for continuous training, reflective supervision, and experience-based professional development to strengthen counselors' self-efficacy. These findings are expected to contribute to improving the quality of individual counseling services in the school environment.